Design of multiband selective near-perfect metamaterial absorbers with SiO2 cylinder/rectangle shell horizontally embedded in opaque silver substrate. (October 2017) - Zhao, Yi; Fu, Ceji
Highlights: Two multiband selective near-perfect thermal radiation absorbers were proposed. Mechanisms for the multiband selective near-perfect absorption were elucidated. Effects of polarization angle and geometric parameters on absorption were explored. Abstract: In this paper, we presented two multiband selective near-perfect absorbers, respectively made of one-dimensional periodic SiO2 cylinder shell and SiO2 rectangle shell arrays horizontally embedded in silver substrate. The spectral-directional absorptivity of the proposed structures was numerically investigated with the finite element based Comsol Multiphysics software. Five near-perfect absorption bands in the wavenumber range from 2500 to 20, 000 cm −1 for TM-wave incidence were obtained for both absorbers. Physical mechanisms responsible for the multiband absorption were elucidated as due to resonance of magnetic polaritons and the effect of Wood's anomaly. Furthermore, the effects of polarization angle and geometric parameters on the multiband selective absorption were explored. This work may provide new guidelines for designing high efficient multiband photodetectors or photon sorters.